Performance Ratio of Photovoltaic Energy Sources in the Application of E-bike Charging Station - Munir, Abdullah Faiq; Hidayat, Mohammad Noor; Imammuddin , Azam Muzakhim; Nugroho, Aji; Heryanto/Eryk , Irwan; Saputra, Masramdhani (International Journal of Frontier Technology and Engineering, 2024)
Solar energy converted by the use of photovoltaic modules, requires testing the performance of the conversion results, to determine the efficiency and performance ratio, when unloaded and loaded. The implementation of this photovoltaic energy source, the researcher aims to use the load of the e-bike at the e-bike charging station with a peak power capacity of 200 Wp PV and a battery storage capacity of 200 Ah 12 V. The test results obtained that PV provides 69% of the load power needs with a peak power of 98.67W at 12.25 WIB, while the battery supplies 31%, with a total PV energy of 0.68 kWh, and the Performance Ratio (PR) of solar panels was obtained at 85.7%. The load of the e-bike itself absorbs 437.6 Wh of energy from SoC charging (62%-100%) with a charging duration of 3.42 hours, where the charging of the e-bike in planning requires 576 Wh of energy for 4.5 hours from the SoC (50%-100%).